Transitional cell carcinoma of the upper urinary tract: a puzzle - Sengupta, Soumish; Basu, Supriya; Ghosh, Kadambari (International Journal of Advances in Medicine, 2020)
Transitional cell carcinoma (TCC) of the upper urinary tract has a puzzling presentation. This is a case report of a 44 year old male with history for smoking 20 pack years presenting with cough, haemoptysis and microscopic haematuria. His sputum was positive for acid fast bacilli. He was treated as pulmonary tuberculosis (PTB) but had gross haematuria a month after initiation of anti-tubercular drugs (ATD). He was investigated with computed tomography (CT) imaging and was found to have thickened renal pelvis and ureter. It was initially thought as a case of genito-urinary tuberculosis (GUTB). Expectant management for gross haematuria failed. The patient was stabilised and taken up for open nephroureterectomy under general anaesthesia (GA). Histopathological report suggested it to be high grade TCC of the left renal pelvis extending to upper ureter. He did well with completion of ATD. He was not started on adjuvant chemotherapy for fear of exacerbation of PTB. He is under regular and uneventful follow up in the outpatient department (OPD).